Hidden breast neoplasm - López Chapuis, Daniel; Laviña, Raúl; Delgado, Fernando; Albo, Manuel (Cirugía del Uruguay, 1990)
The authors present a papel referred to tour patients carrying hidden mammary neoplasma which was detected on/y aher the finding of axillary metastases. They analyze the fact that the axil/ary adenopaty, usual/y a leve/ I one, can be the first clinica/ sign of the illness. They emphasize the importance of paraclinical tests: estrogenic receptor dosage, mammography, termography. They suggest mastectomy -ipsilatera/ to the adenopatyin case of undetected primitive, based on the analysis of international statistics and following Westbrooks algorithm. Final/y, the prognosis is thought to be similar or better than that of palpable tumours with axillary metastases